Cauda Equina Compression an Ayurvedic management w.r.s to Gridrasi and Pakwasaya Gata Vata (International Journal of Ayurveda and Pharma Research, 2022)
Cauda equina compression at the level of L4/L5 or L5/S1 level is a surgical emergency with potentially significant consequences, including motor and sensory dysfunction. The causes include disc herniation, spinal stenosis, cancer, trauma, epidural abscess. The common cause is usually a disc herniation which is most commonly due to trauma, age, connective tissue disorders and congenital disorders. Cauda equina syndrome a disorder caused by compression of the nerve roots in the cauda equina region. This can cause permanent loss of bladder and bowel control if not treated within time. The incidence of a herniated disc is about 5 to 20 cases per 1000 adults annually and is most common in people in their third to the fifth decade of life with a male to female ratio 2:1. If decompressive surgery is delayed, there can be catastrophic consequences for the patient in terms of bladder, bowel and sexual function. In the present case study, a 36 year old female patient who was diagnosed as a case of Cauda Equina compression due to an extruded L4-L5 disc refused to undergo surgery and opted for Ayurvedic treatment. She was admitted in the Kayachikitsa IPD for 45 days. She was treated with the principle of Gridrasi along with Pakwasayagata vata. Deepana pachana and Vasti or Sodhana is the main treatment choice. Rooksha and Snigdha swedas were done which also help to reduce the stiffness and pain. After the management her physical condition and quality of life improved.